2014
DOI: 10.1111/bcpt.12291
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective Effects of Gamma‐Aminobutyric Acid on Cisplatin‐induced Acute Renal Injury in Rats

Abstract: To investigate the effect of gamma-aminobutyric acid (GABA) on acute renal injury (ARI), we used here a rat model of acute tubular necrosis induced by the anticancer drug cisplatin (CP). GABA was given orally (100 or 500 mg/kg/day for ten consecutive days), and on the 6th day, some of the treated rats were also injected intraperitoneally with either saline or CP (6 mg/kg). Four days after CP treatment, urine was collected from all rats, which were then anaesthetized for blood pressure and renal blood flow moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
(54 reference statements)
0
16
0
Order By: Relevance
“…[ 46 ] In the present study, CP alone increases the MDA level of kidney tissue in two genders. When compared with GABA alone, GABA reduces oxidative stress through increased activity of antioxidant enzymes and decreased lipid peroxidation;[ 14 18 ] also, we observed that GABA decreased serum MDA level in male diabetic rats. We are wise that GABA is upper in the male than female.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…[ 46 ] In the present study, CP alone increases the MDA level of kidney tissue in two genders. When compared with GABA alone, GABA reduces oxidative stress through increased activity of antioxidant enzymes and decreased lipid peroxidation;[ 14 18 ] also, we observed that GABA decreased serum MDA level in male diabetic rats. We are wise that GABA is upper in the male than female.…”
Section: Discussionmentioning
confidence: 73%
“…[ 11 ] GABA has vasorelaxant effects[ 17 ] and it can ameliorate CP nephrotoxicity in rats. [ 18 ] GABA exerts antidiabetic effects by acting β-cell restoration and immune suppression[ 19 ] and it could adjust insulin and glucagon secretion and could be used for type 1 diabetes therapy. [ 20 ] In the current study, we investigated the role of GABA in CP-induced nephrotoxicity in STZ-induced diabetic rat model.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress has been known as an important factor to promote cisplatin-induced nephrotoxicity through increasing the accumulation of intracellular ROS [24][25][26]. Under normal physiological conditions, cells control ROS level through balancing the generation of ROS and their elimination by scavenging system [27].…”
Section: Discussionmentioning
confidence: 99%
“…As suggested by this present study and previous ones cited, cisplatin causes high oxidative and nitrosative stress, which explains its toxicity. Therefore, numerous studies have been conducted using antioxidant compounds to attenuate cisplatin‐induced oxidative stress and adverse events . However, it appears that there is still no consensus on whether antioxidants should be administered during cancer treatment as a preventive strategy against the related toxicities of the chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 99%